(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Rheumatoid arthritis (RA) is a systemic chronic, inflammatory disease that may affect many tissues and organs. Objective: To investigate effectiveness and safety of Low-level-laser-therapy (LLLT) in management of early onset RA compared to symptomatic non-steroidal anti-inflammatory drugs (NSAIDS) therapy. Methods: A convenient selection 3 arms single blinded trial conducted in Al-Saraj Center for Rheumatoid Diseases in Baghdad during period between January-May 2017. Thirty-four patients with RA onset below one year were recruited. Disease activity score (DAS28) formula with American College of Rheumatology criteria (ACR20), erythrocyte sedimentation rate (ESR), visual analogue scale (VAS), complete blood count (CBC), C-reactive protein (CRP), rheumatoid factor (RF) were measured. Patients were divided into three groups: group 1 (n=12) received LLLT, group 2 (n=12) received placebo laser and naproxen and group 3 (n=10) received only naproxen. Primary outcomes measured were disease activity using DAS28 score, clinical improvement using ACR20 and pain assessment using VAS. Secondary outcomes measured were remission ACR50 and 70 and inflammatory indicators. Results: LLLT group has shown significant decrease of DAS28 (P=0.02), morning stiffness duration (p=0.05), number of tender joints (p=0.03), number of swelling joints (p=0.04), and VAS (p=0.01) compared to baseline whereas placebo laser group with naproxen and naproxen only group showed only significant reduction in duration of morning stiffness(P=0.04) and (p=0.048) respectively. There was marginal lowering of ESR (P=0.06) in LLLT group but no changes in CRP, RF. There were no reported side effects of LLLT use. Conclusion: Laser therapy is better than NSAIDS in controlling RA symptoms with no associated side effects. Therefore, it is recommended as first-line therapy in early onset RA. Keywords: laser, Low level laser therapy, rheumatoid arthritis, NSAIDS, ESR, Nerve root Citation: Al-Saraj MJA, Al-Ethary ZY, Al-Attar ZI. the effect of low level laser therapy on early onset rheumatoid arthritis patients. Iraq Iraqi JMS. 2021; 19(1): 126-133. doi: 10.22578/IJMS.19.1.16